Implementation of the Sulaimaniyah Curriculum in Developing Children’s Competencies at Enderun Islamic Preschool - Naja Naqia; Dewi Fitriani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
The curriculum is a plan or framework that determines what will be taught in education. The curriculum serves as a guideline that establishes the direction, educational goals, and the materials that need to be learned. Enderun Islamic is a Kindergarten that not only implements the Merdeka Curriculum but also integrates the Turkish curriculum. This research aims to analyze the implementation of the Sulaimaniyah curriculum in developing children's competencies at Enderun Islamic Preschool. Using a qualitative approach, a case study research type was selected to explore the unique and specific implementation of the Sulaimaniyah curriculum in this institution. Data collection techniques were carried out through interviews, observations, and documentation. The subjects of this research were the principal and one of the teachers at Enderun Kindergarten. Data analysis was conducted using the Milles & Huberman technique, which includes three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Sulaimaniyah curriculum implements religion-based and character education, the stages of the Sulaimaniyah curriculum, flagship programs of the Sulaimaniyah curriculum, learning media sourced directly from Turkey, and the evaluation of the Sulaimaniyah curriculum.